Changes in skeletal and cardiac muscle enzymes during the Scottish Coast to Coast Triathlon - Denvir, M. A.; Galloway, P. J.; Meighan, A. S.; Blyth, M.; Alexander, C.; Fleming, C.; Frame, F. (Scottish Medical Journal, 1999)
While skeletal muscle injury is common after prolonged exercise, evidence in the literature supporting cardiac muscle injury is conflicting. Creatine kinase and cardiac troponin-I were measured, in 31 amateur athletes (25 male) before, and 12-24 hours after, a 300 km cycling/running/canoe triathlon event. A short questionnaire was used to assess level of fitness, training and previous experience. Creatine kinase levels were greater after the 45 km cross-country run compared with after a 155 km road cycle (60.5 +/- 62.8 iu/L/kg vs 19.3 +/- 9.6 iu/kg, P = 0.03). Individuals performing running and cycling events consecutively had creatine kinase similar to those observed after running alone (50.2 +/- 53.8 iu/L/kg vs 60.5 +/- 62.8 iu/L/kg, P = 0.55). Cardiac troponin-I was elevated above the normal range (0.1 ng/L) in six athletes (four in running and cycling events, one in the running and one in the cycling event). We conclude that running produces significantly more skeletal muscle injury than cycling and that strenuous endurance exercise involving running and cycling in amateur trained athletes is associated with release of cardiac specific enzymes. The functional and longer term consequences of this require further study.